Analytical Solutions of Fractional Differential Equations Using the Convenient Adomian Series - Xiang-Chao Shi; Lan-Lan Huang; Zhen-Guo Deng; Dan Liu (Abstract and Applied Analysis)
Due to the memory trait of the fractional calculus, numerical or analytical solution of higher order becomes very difficult even impossible to obtain in real engineering problems. Recently, a new and convenient way was suggested to calculate the Adomian series and the higher order approximation was realized. In this paper, the Adomian decomposition method is applied to nonlinear fractional differential equation and the error analysis is given which shows the convenience.